2013
DOI: 10.1039/c3mt20205d
|View full text |Cite
|
Sign up to set email alerts
|

Selenite and tellurite form mixed seleno- and tellurotrisulfides with CstR from Staphylococcus aureus

Abstract: Staphylococcus aureus CstR (CsoR-like sulfur transferase repressor) is a member of the CsoR family of transition metal sensing metalloregulatory proteins. Unlike CsoR, CstR does not form a stable complex with transition metals but instead reacts with sulfite to form a mixture of di- and trisulfide species, CstR2(RS-SR′) and CstR2(RS-S-SR′)n, n = 1 or 2, respectively. Here, we investigate if CstR performs similar chemistry with related chalcogen oxyanions selenite and tellurite. In this work we show by high res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 46 publications
1
36
0
Order By: Relevance
“…Similarly, CstR will form disulfides, selenotrisulfides, tellurotrisulfides when reacted with the calcogen oxyanions selenite and tellurite, respectively (Figure 3B). 29 These crosslinked products were not observed in CsoR. 6,29 Work done by Luebke et al showed that Cys31 initiates the reaction with sulfite through the formation of S -sulfocysteine (Figure 3B).…”
Section: Cstrmentioning
confidence: 97%
See 2 more Smart Citations
“…Similarly, CstR will form disulfides, selenotrisulfides, tellurotrisulfides when reacted with the calcogen oxyanions selenite and tellurite, respectively (Figure 3B). 29 These crosslinked products were not observed in CsoR. 6,29 Work done by Luebke et al showed that Cys31 initiates the reaction with sulfite through the formation of S -sulfocysteine (Figure 3B).…”
Section: Cstrmentioning
confidence: 97%
“…29 These crosslinked products were not observed in CsoR. 6,29 Work done by Luebke et al showed that Cys31 initiates the reaction with sulfite through the formation of S -sulfocysteine (Figure 3B). 29 They also determined that modify-cation of Cys31 (in a Cys60A background) with the cysteine-modifying reagent methylmethanethiosulfonate (MMTS) resulted in a decrease in DNA binding affinity while similar modifications to Cys60 had no effect on DNA binding affinity.…”
Section: Cstrmentioning
confidence: 97%
See 1 more Smart Citation
“…Normalized r values (ranging from 0 to 1) represent fractional saturation of the DNA and were calculated from the ratio (r obs Ϫ r DNA )/(r max Ϫ r DNA ), where r max is the maximum anisotropy obtained at saturating protein concentrations, and r DNA is the anisotropy of the free DNA. The resultant data were subjected to an unweighted nonlinear least squares fit to a two-tetramer binding model (defined by K 1 and K 2 ) as described earlier (16,25) using the program DynaFit (43) and assuming a linear relationship between r obs and fractional saturation of the DNA as verified previously (16). The macroscopic DNA binding constant, A 2 , is determined from A 2 ϭ K 1 ⅐K 2 (see Table 1 …”
Section: Methodsmentioning
confidence: 99%
“…A second M. tuberculosis CsoR paralog, RicR, was shown to be involved in the regulation of several genes only found in pathogenic mycobacteria in response to copper stress (2). Several non-copper-sensing CsoR-like proteins, including the nickel-sensing repressors RcnR in Escherichia coli (21,22) and InrS in Synechocystis (23) and the sulfur transferase regulator CstR in S. aureus (24,25), have also been identified, revealing that this family of proteins has evolved to sense a range of inducers.…”
mentioning
confidence: 99%